Urinary 8-oxo-7,8-dihydroguanosine as a Potential Biomarker of Aging - Gan, Wei; Liu, Xin-Le; Yu, Ting; Zou, Yuan-Gao; Li, Ting-Ting; Wang, Shuang; Deng, Jin; Wang, Lan-Lan; Cai, Jian-Ping (Frontiers in Aging Neuroscience, 2018)
BACKGROUND: A molecular biomarker of physiologic age, as opposed to chronologic age, is needed in clinical medicine. 8-oxo-7,8-dihydro-2’-deoxyguanosine (8-oxodGuo) and 8-oxo-7, 8-dihydroguanosine (8-oxoGuo) are two promising aging biomarkers. METHODS: A total of 1228 healthy Chinese residents (613 males and 615 females) 2 to 90 years of age were randomly selected. Spot urine samples were collected, and the concentrations of 8-oxodGuo and 8-oxoGuo were measured using ultra-high-performance liquid chromatography with a triple quadrupole mass spectrometer (UPLC-MS/MS). Method validation, including accuracy, precision, linearity and quantiﬁcation limit, was performed. The relationship between oxidized guanosine and age/gender was evaluated. RESULTS: 8-OxodGuo and 8-oxoGuo were eluted at 1.61 and 1.30 minutes, respectively. The calibration curve was linear in the range of 0.2–500 ng/ml for both analytes. The lowest limit of quantification (LLOQ) was 0.2 ng/ml for 8-oxodGuo and 0.1 ng/ml for 8-oxoGuo. There was an age-dependent increase in the biomarkers from the 21- to 30-year-old group to the 81- to 90-year-old group in both genders. In the subjects older than 61 years of age, the levels of 8-oxodGuo as well as 8-oxoGuo in urine were much higher in females than in males. The content of 8-oxoGuo correlated more closely with age and was higher (approximately 2-fold) than that of 8-oxodGuo for a given individual. CONCLUSIONS: 8-oxodGuo and 8-oxoGuo can be easily measured by UPLC-MS/MS. Urinary 8-oxoGuo may be a potential biomarker to determine a person’s physiologic age and identify individuals at high risk of developing age-associated disease.